Multi-level Hierarchical Structure Analysis of Influencing Factors of Coal Mine Managers' Blame Avoidance Behavior - Li Wang; Wenyi Zeng; Ziyan Jing; Yonghui Xu; Jiang Li (Elsevier, 2024)
Background: In the Chinese coal industry, widespread blame avoidance behavior (BAB) greatly impacts coal mine accidents. Therefore, it is necessary to stop the BAB of coal mine managers and raise the management level of coal mine enterprises for the safe development of Chinese coal industry. Methods: Based on the semi-structured interviews and questionnaire surveys (20 middle-level managers in coal mines), this paper used the Grounded Theory and Nvivo Software qualitative research methodology to open, spindle, and selectively encode the interview data. Then, an index system of factors influencing BAB of coal mine managers was constructed. The influence degree, affected degree, centrality degree, cause degree of each influencing factor were calculated and the hierarchical model of influencing factors of BAB of coal mine managers was established by the DEMATEL-ISM method which is a decision support tool used to evaluate and analyze the interdependencies between influencing factors. Results: Index system of factors influencing BAB of coal mine managers included four levels and 12 influencing factors: individual, organizational, institutional environmental, and situational factors. The hierarchical model identified eight causal factors and four consequential factors, of which safety management (15.355), work attitude (14.380), and work group performance (14.281) in the top three of the centrality rankings are the key factors affecting the avoidance behavior of coal mine managers; A 3-level multilevel structure was constructed to reflect the interactions among the factors influencing the BAB of coal mine managers in terms of direct, indirect, and root causes, and corresponding improvement measures were proposed. Conclusion: This study offers a theoretical complement and practical guidance for stopping BAB of coal mine managers.